2019
DOI: 10.1093/brain/awz346
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid tau fragment correlates with tau PET: a candidate biomarker for tangle pathology

Abstract: To date, there is no validated fluid biomarker for tau pathology in Alzheimer’s disease, with contradictory results from studies evaluating the correlation between phosphorylated tau in CSF with tau PET imaging. Tau protein is subjected to proteolytic processing into fragments before being secreted to the CSF. A recent study suggested that tau cleavage after amino acid 368 by asparagine endopeptidase (AEP) is upregulated in Alzheimer’s disease. We used immunoprecipitation followed by mass spectrometric analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 40 publications
3
75
0
2
Order By: Relevance
“…To test whether the alterations in soluble tau metabolism also involved a differential truncation of tau, we measured a C-terminally truncated variant of tau, ending at amino acid 368 (called Tau 368 ), which is enriched in NFT (23), using a recently described singlemolecule array assay (24). The results are shown in fig.…”
Section: Csf Levels Of Truncated Taumentioning
confidence: 99%
“…To test whether the alterations in soluble tau metabolism also involved a differential truncation of tau, we measured a C-terminally truncated variant of tau, ending at amino acid 368 (called Tau 368 ), which is enriched in NFT (23), using a recently described singlemolecule array assay (24). The results are shown in fig.…”
Section: Csf Levels Of Truncated Taumentioning
confidence: 99%
“…In one study, N-terminal tau fragment truncated at 224 amino acids (N-224) colocalised to neurofibrillary tangles in brain extracts and showed significantly higher levels in CSF from patients with AD in comparison to controls, with higher baseline levels predictive of steeper cognitive decline [24]. More recently, tau N-368 has also been found to be significantly elevated in CSF of AD patients, with a ratio of tau N-368 to total tau exhibiting a strong negative correlation with tau PET [25]. AD pathology also significantly affects phosphorylation patterns, with hyperphosphorylation seen of a number CSF tau sites in comparison to healthy controls.…”
Section: Csf Taumentioning
confidence: 99%
“…Interestingly, the level of MC1 reactivity correlates with the severity and progression of AD. To our knowledge, no assay has been developed to detect this early marker of pathology in biofluids, likely due to the possibility that tau truncated species [ 205 , 206 , 207 , 208 ] could prevent the identification of a conformational tau epitope using the currently available immunoassays, which are-based primarily on mid-region-directed antibodies. We believe that, although this pathological feature is not per se easily “translatable”, it should be kept in consideration when designing and developing new tau biomarkers platforms.…”
Section: Biomarkers Of Ad Pathologymentioning
confidence: 99%
“…The authors were able to demonstrate that mid-region- and N-terminal-containing fragments increase with disease, while full-length tau is just a small fraction of the tau present in both normal and AD CSF. A recent study has also shown that the ratio between C-terminally truncated tau368 and t-tau is significantly decreased in patients with Alzheimer’s disease, with a strong correlation with 18 F-GTP1 retention in brain [ 207 ] (a measure of tangle pathology in vivo); these data suggest that tau fragment may preferentially accumulate in tangles, and the CSF ratio tau368/t-tau reflects tangle pathology in brain and can be used as an additional tau biomarker to stage and improve the diagnosis of Alzheimer’s disease.…”
Section: Biomarkers Of Ad Pathologymentioning
confidence: 99%